Instantaneous Cardiac Baroreflex Sensitivity: xBRS Method Quantifies Heart Rate Blood Pressure Variability Ratio at Rest and During Slow Breathing - Wessel, Niels; Gapelyuk, Andrej; Weiß, Jonas; Schmidt, Martin; Kraemer, Jan F.; Berg, Karsten; Malberg, Hagen; Stepan, Holger; Kurths, Jürgen (Frontiers in Neuroscience, 2020)
To quantify spontaneous baroreflex sensitivity (BRS), many groups use the xBRS method, which calculates the cross-correlation between the systolic beat-to-beat blood pressure and the R-R interval, resampled at 1 Hz, in a 10 s sliding window, with 0-5 s delays for the interval. The delay with the greatest positive correlation is selected and, if signiﬁcant, the quotient of the standard deviations of R-R intervals and systolic blood pressures are recorded as corresponding xBRS value. In this paper we test the hypothesis that the xBRS method quantifies the causal interactions of spontaneous BRS at rest and is not exclusively dominated by the quotient of heart rate and systolic blood pressure variability (HRV/BPV). Therefore, we retrospectively analyzed 1828 beat-to-beat time series and the corresponding systolic blood pressure at rest. We found a high correlation between the HRV/BPV quotient and the xBRS of r=0.94 (p<0.001). Two different surrogate analyses showed that the xBRS method is not able to quantify causal relationships between the two signals; it cannot distinguish between random and baroreflex controlled sequences but rather determines the HRV/BPV quotient. We conclude that the xBRS method has a potentially large bias in characterizing the capacity of the arterial baroreflex under resting conditions. During slow breathing, estimates for xBRS are significantly increased, which clearly shows that measurements at rest only involve limited baroreflex activity but does neither challenge nor show the full capacity of the arterial baroreflex. We show that xBRS is exclusively dominated by the heart rate to systolic blood pressure ratio (r=0.965, p<0.001). Further investigations will show whether certain autonomous testing procedures such as slow breathing or orthostatic testing can serve as a basis for a non-invasive evaluation of baroreflex sensitivity.